INFLUENCE OF ORGANIC ACIDS ON THE BIOSINTHESIS OF AMINO ACIDS BY CORYNEFORM BACTERIUM (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
The effect of organic acids on the growth of some coryneform bacteria and on the biosynthesis of amino acids have been studied. It was shown that the organic acids (lactic, acetic, citric) in the synthetic nutrient medium in the concentrations 0.5–1.0% were assimilated by the strain producers of     L-proline, L-ornithine, L-serine and L-arginine. Their presence in the nutrient medium influences on the biosynthesis of amino acids differently.
Keywords: organic acids; coryneform bacteria; biosynthesis; biosynthesis of amino acids